Common Defense - Ruggero, Ed (New York : Pocket Books, 1992)
In Mexico to instruct its army on counterterrorism techniques, army veteran Captain Mark Isen finds his mission expanded by the arrival of German terrorist Heinrich Wolf and his deadly attacks on the United States
70949
Keywords: Terrorism -- Fiction; Spies & Political Thrillers; Literature & Fiction; Adventure stories